2008
DOI: 10.2174/157017808785982194
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and Docking Studies on Propenone Derivatives as Dual COX and 5- LOX Inhibitors

Abstract: Quantitative structure activity relationships were developed for seventeen propenone derivatives reported in the literature that act as dual COX and 5-LOX inhibitors. Predominantly spatial, thermodynamic, topological, and electronic descriptors appear in the models. Docking between these compounds and COX-1, COX-2 and 5-LOX enzymes was also performed and mathematical relationships were developed between the binding energy and activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…From their studies, they demonstrated that the physicochemical properties Hy (hydrophilic factor) and Mor17v (3D molecular representation of structure based on electron diffraction code) are important for more dual COX-2/5-LOX inhibitory activity. Further Mukesh Doble and his group developed QSAR model of seventeen propenone derivatives [ 117 ], which were reported to be COX-2/5-LOX dual inhibitors [ 98 ]. A training set of 13 compounds was used in their study.…”
Section: Application Of Lbdd In 5-lox Inhibitor Developmentmentioning
confidence: 99%
“…From their studies, they demonstrated that the physicochemical properties Hy (hydrophilic factor) and Mor17v (3D molecular representation of structure based on electron diffraction code) are important for more dual COX-2/5-LOX inhibitory activity. Further Mukesh Doble and his group developed QSAR model of seventeen propenone derivatives [ 117 ], which were reported to be COX-2/5-LOX dual inhibitors [ 98 ]. A training set of 13 compounds was used in their study.…”
Section: Application Of Lbdd In 5-lox Inhibitor Developmentmentioning
confidence: 99%